(untitled) (Boletin Médico de Postgrado, 2020)
Upper urinary tract urothelial carcinoma (UC) is infrequent and represents only 5%-10% of all UCs. These neoplasms grow from the urothelium of renal calyces to the distal third of the ureter. A case of UC of the upper urinary tract is reported in a 68-year-old male patient with a 3-month history of left lumbar mild to moderate pain, which partially mitigates with the use of NSAIDs associated with visible total predominantly nocturnal hematuria. Macroscopic hematuria was evident and urinary cytology reported carcinoma suggestive atypias. Contrasted CT of abdomen and pelvis showed filling defect in relation to lower calyx of the left kidney and left para-aortic ganglion plastron. Radical left nephroureterectomy was performed showing a 3 x 3 x 1 cm tumor in relation to the renal pelvis extending to the lower cavity and invading renal parenchyma. Histopathology showed high grade infiltrative papillary CU with margins without lesions and lymph nodes with metastasis. Patient evolves satisfactorily in the postoperative period and is currently in adjuvant therapy. Although this pathology is rare, it can occur and the urologist must be able to face it.